Severe Progressive Diffuse Alveolar Hemorrhage in a Patient with Systemic Lupus Erythematosus - Munenori Kusunoki; Takeshi Umegaki; Tomohiro Shoji; Kota Nishimoto; Natsuki Anada; Akiko Ando; Takeo Uba; Kanako Oku; Saya Hakata; Satoshi Hagihira; Takahiko Kamibayashi (Case Reports in Critical Care)
Diffuse alveolar hemorrhage (DAH) refers to the effusion of blood into the alveoli due to damaged pulmonary microvasculature. The ensuing alveolar collapse can lead to severe hypoxemia with poor prognosis. In these cases, it is crucial to provide respiratory care for hypoxemia in addition to treating the underlying disease. Here, we describe our experience with a case involving a 46-year-old woman with severe DAH-induced hypoxemia accompanying systemic lupus erythematosus (SLE). Mechanical ventilation was managed using airway pressure release ventilation (APRV) after intubation. Through APRV-based respiratory care and treatment of the underlying disease, hemoptysis was eliminated and oxygenation improved. The patient did not experience significant barotrauma and was successfully weaned from mechanical ventilation after 25 days in the intensive care unit. This case demonstrates that APRV-based control for respiratory management can inhibit the effusion of blood into the alveoli and achieve mechanical hemostasis, as well as mitigate alveolar collapse. APRV may be a useful method for respiratory care in patients with severe DAH-induced hypoxemia.